Modern equipment for construction of airlines - Chepak, A. (ТДАТУ, 2021)
The community is currently living in an era of progressive energy crisis. However, the intensive use of non-renewable energy sources for heating, vehicles, road construction machinery, agricultural machinery and various household appliances, produces a huge amount of oxides of carbon, sulfur and nitrogen. All this contributes to rising temperatures of the earth's and water's surface, causes environmental pollution, acid rain, and stimulates intense melting of ice, rising ocean levels, flooding of vast land areas, the emergence of cyclones and hurricanes covering entire continents. Therefore, the development of alternative energy solutions based on non-traditional approaches, as well as with the use of renewable sources is important. Research in the use of renewable energy sources is associated with the creation and practical application of solar and wind installations, hydroelectric power plants and various types of converters. The energy resources produced in this case, in addition to the intended use, can also be accumulated by various storage systems.
Keywords: energy sources; environmental pollution